Anti-infectives derived from botanical natural products: an interview with Cassandra Quave. (September 2018) - Greenway, Alice; Quave, Cassandra Leah
The editor of Future Microbiology, Alice Greenway, speaks to Cassandra Quave from Emory University (GA, USA) following her talk entitled 'Discovery of Anti-infectives and Virulence Inhibitors from Botanical Natural Products' at American Society for Microbiology (ASM) Microbe 2018 (7–11 June).